2022
DOI: 10.5897/ajar2022.15972
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of medium maturity group of soybean (Glycine max L. Merr) for agronomic performance and adaptation in Sudanian zone of Burkina Faso

Abstract: Soybean is an economically important crop that provides oil and high-quality protein. In Burkina Faso, soybean is one of the promising crops identified in the framework of the strategy for the development of agricultural sectors. However, very few improved varieties have been developed. The identification of newly improved varieties with high agronomic potential and adapted to the climatic conditions will strengthen soybean production in the country. The objective of this study was to evaluate the agronomic pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…Results showed that 7 genotypes of soybean were the earliest (45-48 days) and better than the control early genotype G175 (50 days). Compared with previous work, the early maturity check genotype G175 took fve 5 days more in the climatic condition of Burkina Faso to reach 50% fowering [14]. Tis result is suggesting a probable photoperiod sensitivity observed for that genotype.…”
Section: Variability Of Phenological Traitscontrasting
confidence: 57%
See 2 more Smart Citations
“…Results showed that 7 genotypes of soybean were the earliest (45-48 days) and better than the control early genotype G175 (50 days). Compared with previous work, the early maturity check genotype G175 took fve 5 days more in the climatic condition of Burkina Faso to reach 50% fowering [14]. Tis result is suggesting a probable photoperiod sensitivity observed for that genotype.…”
Section: Variability Of Phenological Traitscontrasting
confidence: 57%
“…As a consequence, the management of pod shattering is of great importance for achieving higher productivity and reducing yield losses [33]. Globally, the genotypes of the early maturity group of soybean seem more sensitive to pod shattering than those of the medium maturity group, as shown by the work of [14]. In general, pod shattering is afected by diferent environmental factors (dry climate, low humidity, high temperature, and rapid temperature changes) and irrigation systems [34,35].…”
Section: Variability Of Pod Shatteringmentioning
confidence: 99%
See 1 more Smart Citation